2017
DOI: 10.1097/mpg.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

European Society for Paediatric Gastroenterology, Hepatology and Nutrition Guidelines for the Evaluation and Treatment of Gastrointestinal and Nutritional Complications in Children With Neurological Impairment

Abstract: Thirty-one clinical questions addressing the diagnosis, treatment, and prognosis of common gastrointestinal and nutritional problems in neurological impaired children were formulated. Questions aimed to assess the nutritional management including nutritional status, identifying undernutrition, monitoring nutritional status, and defining nutritional requirements; to classify gastrointestinal issues including oropharyngeal dysfunctions, motor and sensory function, gastroesophageal reflux disease, and constipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
465
0
47

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(518 citation statements)
references
References 214 publications
(361 reference statements)
6
465
0
47
Order By: Relevance
“…Many authors reported that children with CP were prone to stunted growth, independent of their nutritional status. 19,21 Further research is needed to determine the most reliable and applicable tools to recognize undernutrition in children with CP. Therefore, we suggest using stunted growth as an indicator for undernutrition in children with CP with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported that children with CP were prone to stunted growth, independent of their nutritional status. 19,21 Further research is needed to determine the most reliable and applicable tools to recognize undernutrition in children with CP. Therefore, we suggest using stunted growth as an indicator for undernutrition in children with CP with caution.…”
Section: Discussionmentioning
confidence: 99%
“…16 Unfortunately, there is no widely accepted consensus as to which cut-off for the BMI z-score should be used to identify undernutrition (e.g. 19 They stated that 'the assessment of nutritional status in children with neurological impairment should not be based solely on weight and height' and recommended that the measurement of fat mass should be a routine component of the nutritional assessment. 17,18 Recently, the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition reported guidelines for the evaluation and treatment of gastrointestinal and nutritional complications in children with neurological impairment, where CP was considered as a proxy.…”
mentioning
confidence: 99%
“…However in the pediatric age, contradictory findings on different anthropometric measures and cardiometabolic risk association have been reported. European Society for Pediatric Gastroenterolgy Hepatology and Nutrition (ESPGHAN) Guidelines for the Evaluation and Treatment of Gastrointestinal and Nutritional Complications in Children with Neurological Impairment [26] recommend using skinfold thickness rather than BMI for nutritional assessment in NI children, which provides better estimates of body fat. The guidelines also underscore that their interpretation is very challenging because children with NI tend to store fat more centrally (abdomen) than peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, например, что у детей с GMFCS III-V уровня и массой тела < 20-го перцен-тиля риск смерти в 1,5 раза выше, чем у детей с нормальны-ми показателями физического развития [28]. В этой связи можно предположить, что при наличии таких антропоме-трических показателей у ребенка с ДЦП необходимо про-ведение нутритивных вмешательств (назначение высоко-калорийных смесей, зондовое питание, установка стом) [29].…”
Section: вопросы современной педиатрииunclassified
“…Кроме того, преимуществом специализированных центильных шкал является возмож-ность выявления ребенка с церебральным параличом, имеющим недостаточность питания, и выполнение реко-мендаций Европейского общества детских гастроэнтеро-логов, гепатологов и нутрициологов (European Society for Paediatric Gastroenterology and Hepatology and Nutrition, ESPGHAN) по диагностике и лечению детей, имеющих гастроинтестинальные и нутритивные осложнения при неврологической патологии. Так, согласно рекомендаци-ям [29], врачу-педиатру при выявлении БЭН, высокого риска аспирации, аспирационной пневмонии в анамнезе, подозрении на дисфагию необходимо направить ребенка на консультацию к врачу-оториноларингологу для решения вопроса о флуороскопии и постановке гастростомы.…”
Section: вопросы современной педиатрииunclassified